The effect of single-task versus dual-task assessment on muscle strength and performance in individuals with knee osteoarthritis. - Genç PhD, Hazal; Demircioğlu PhD, Gamze (Physiotherapy Theory & Practice, 2025)
Background: Dual-task activities, which involve performing two separate tasks simultaneously, often result in reduced motor function and daily activity performance among individuals with knee osteoarthritis (OA). Objective: This study aimed to investigate the impact of single- and dual-task conditions on muscle strength and performance in individuals with knee OA and examine how cognitive load influences physical task performance in this population. Methods: Sixty patients with knee OA were included. Baseline data included demographic characteristics, pain (Visual Analog Scale), and physical function (Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC)). Muscle strength and performance were assessed using isokinetic and sit-to-stand tests, initially under single-task conditions, and then under dual-task conditions three days later. Dual-tasking involved physical tasks with varying cognitive exercises (changed between sessions) and familiarization sessions to minimize learning effects. Results: The investigation revealed that individuals with knee OA showed reduced muscle strength and impaired sit-to-stand performance during dual-task activities, with lower peak torque (p =.0025), total work (p =.026), and longer time to peak torque (p =.011). Decreased muscle performance correlated with worse WOMAC scores (p ≤.01, r = -0.506), particularly in dual-task conditions. Regression analysis identified extension total work and the sit-to-stand test as key predictors of dual-task performance, explaining 32.2% of the variance. Conclusion: Dual-task performance impairs muscle strength and physical function in individuals with knee OA, demonstrated by reduced peak torque, total work, and sit-to-stand performance. Extension total work and sit-to-stand test emerged as key predictors of dual-task performance, emphasizing the need to address cognitive load in rehabilitation strategies.